ANALISIS PELAYANAN TERHADAP OMZET PENJUALAN BATIK PADA TIRTA BATIK YOGYAKARTA - Hartadi, Agung; Nugroho, Nurhadi; Subandi, Subandi (LPPM Akademi Manajemen Administrasi Yogyakarta, 2022)
Service analysis on batik sales revenue in Tirta Batik Yogyakarta. Service affects batik sales revenue because with the emergence of a good sense of service, customers will feel happy and comfortable using Tirta Batik's services and products so that the quality provided and the sense of service provided by customers will affect sales revenue. The sample in this study was 45. Using the SPSS Statistics IMB tool 22. The results showed that there was a significant influence between service and batik sales revenue which was carried out on the t test. From the results obtained t count of 4.889 and t table of 1.6810, so that 4.889 > 1.6810. or t count is greater than t table so that it is concluded that ho is rejected and ha is accepted. The magnitude of the effect of service on batik sales is 35.7%. From the results of data processing the value of R Square (coefficient of determination) is 0.357 or 35.7%. and the remaining 64.3% is influenced by other variables.